R : unleash machine learning techniques : find out how to build smarter machine learning systems with R : follow this three module course to become a more fluent machine learning practitioner : a course in three modules.: unleash machine learning techniques : find out how to build smarter machine learning systems with R : follow this three module course to become a more fluent machine learning practitioner : a course in three modules. (2016) - Bali, Raghav; Sarkar, Dipanjan; Lantz, Brett; Lesmeister, Cory
No abstract available